Nutrition for athletes (2003)
Whenever highly talented, motivated and well trained athletes gather for competition, the margin between victory and defeat is small. Attention to detail can make that vital difference. Diet affects performance, and the foods that we choose in training and competition will affect how well we train and compete. Athletes need to be aware of their nutritional goals and of how they can select an eating strategy to meet those goals. Diet may have its biggest impact on training, and a good diet will help support consistent intensive training without the athlete succumbing to illness or injury. Good food choices can also promote adaptations to the training stimulus. Athletes are all different, and there is no single diet that meets the needs of all athletes at all times. Individual needs also change across the season and athletes must be flexible to accommodate this. Getting the right amount of energy to stay healthy and to perform well is key. Too much and body fat increases: too little and performance falls and illness results. Carbohydrate is a key nutrient for energy supply. Athletes must be aware of foods that can help meet their carbohydrate needs and make these a focus of their diet. Protein foods are important for building and repairing muscles, but a varied diet containing everyday foods will generally supply more than enough protein. Well-chosen vegetarian diets can also meet protein needs. A varied and wholesome nutrient-rich diet that meets energy needs and is based largely on vegetables, fruits, beans, legumes, grains, animal meats, oils and carbohydrate should ensure an adequate intake of vitamins and minerals. Maintaining hydration is important for performance. Fluid intake before, during (where appropriate) and after exercise is especially important in hot climates. Salt replacement is important when sweat losses are high. Athletes are cautioned against the indiscriminate use of dietary supplements. This booklet contains information that will help athletes to make informed choices to meet their nutritional needs in different situations. It is no substitute for individual advice from a qualified professional, but tries to give practical information that will be of use to the serious athlete.